2016
DOI: 10.1002/oca.2269
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic model predictive control approaches applied to drinking water networks

Abstract: Control of drinking water networks is an arduous task given their size and the presence of uncertainty in water demand. It is necessary to impose different constraints for ensuring a reliable water supply in the most economic and safe ways. To cope with uncertainty in system disturbances due to the stochastic water demand/consumption, and optimize operational costs, this paper proposes three stochastic model predictive control (MPC) approaches, namely: chance-constrained MPC, tree-based MPC, and multiplescenar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 40 publications
0
30
0
1
Order By: Relevance
“…This has rendered the use of SSMPC prohibitive and has hindered its applicability. Indeed, hitherto there have been used only conventional model predictive control approaches [14,15], robust worst-case formulations [5,16,17] and stochastic formulations where the underlying uncertainty is assumed to be normally identically independently distributed [18,19]. Note that it has been observed that demand prediction errors are typically follow heavy-tail distributions which cannot be well approximated by normal ones [20].…”
Section: State Of the Artmentioning
confidence: 99%
See 2 more Smart Citations
“…This has rendered the use of SSMPC prohibitive and has hindered its applicability. Indeed, hitherto there have been used only conventional model predictive control approaches [14,15], robust worst-case formulations [5,16,17] and stochastic formulations where the underlying uncertainty is assumed to be normally identically independently distributed [18,19]. Note that it has been observed that demand prediction errors are typically follow heavy-tail distributions which cannot be well approximated by normal ones [20].…”
Section: State Of the Artmentioning
confidence: 99%
“…It is common in stochastic control-oriented modeling to assume that the errors j|k are independently distributed [18,19]. This assumption however neglects the covariance across the times stages -indeed, if at the future time j = 1 the model has a large prediction error we would rather expect that the prediction error at time j = 2 is likely to be large too.…”
Section: Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…El controlador MPC puede considerar retardos en las entradas y salidas, no linealidades, incertidumbres, naturaleza estocástica, por nombrar algunos (Grosso, et al, 2016); (Camacho & Bordons, 2004); (Velarde, et al, 2017). La idea detrás de este esquema de control es minimizar una función objetivo mediante el cálculo de una secuencia de acciones de control a lo largo de un horizonte de predicción; solo el primer componente de esta secuencia de control se implementa en el paso de tiempo actual; las acciones de control restantes se descartan.…”
Section: Introductionunclassified
“…An application of this technique in the context of the drinking water network of the city of Barcelona is reported in [28]. In addition, [29] shows a comparison between MS-MPC, TB-MPC, and CC-MPC approaches applied to drinking water networks via simulation. Further, this subject has drawn significant interest; a stochastic optimization model implemented in the context of the control of microgrids can be seen in [30][31][32][33] and references therein.…”
Section: Introductionmentioning
confidence: 99%